The Impact of Digital Marketing on Perceived Competitive Performance: The Mediating Role of Marketing Innovation Among Iraqi Consumers Using Digital Applications - Zaid Yaseen Saud (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
Digital marketing is an essential strategic instrument used by businesses to increase their perceived competitive performance in increasingly volatile markets. In emerging countries like Iraq, the development of digital technologies and social media has drastically impacted consumer behavior and marketing strategies. Therefore, this research intends to investigate the effect of digital marketing on perceived competitive performance through the mediating effect of marketing innovation among consumers using digital applications in Iraq. The data collected in this research consists of 412 valid samples. Data analysis was carried out using the Statistical Package for Social Sciences (SPSS) version 26. Digital marketing is found to have a significant positive effect on perceived competitive performance. Moreover, marketing innovation was found to partially mediate the relationship between digital marketing and perceived competitive performance. Besides, high reliability and validity measures of the measurement model were validated in this study. This research provides an important contribution to the literature on digital marketing. This research has explored the concept of digital marketing in a developing country, Iraq, which has not been addressed in previous studies.